PSYCHOANALYSIS OF RANDOLPH “RANN” COLFAX’S PERSONALITY IN PEARL S. BUCK NOVEL “THE ETERNAL WONDER” - Fajrin, Naufal; Weda, Sukardi; Iskandar, Iskandar (State University of Makassar, 2024)
In this study, the researcher analyzed the personality of the main character in a literary work. The researcher examined two issues, namely: (1) What are the personality structures of Randolph